X,γ,β–spectrometric investigations of Chernobyl “hot particles” nuclide composition - Bondarenko, V.N.; Glygalo, V.N.; Goncharov, A.V.; Goncharov, I.G.; Kolot, V.Ya.; Mazilov, A.V.; Rudya, K.G.; Sukhostavets, V.I.; Tolstolutsky, A.G. (Вопросы атомной науки и техники, 2001)
Results of investigation of the radionuclide composition of “hot particles” from Chernobyl “Shelter” Object are discussed. An estimate of radionuclide activity of radioactive pollution levels for some premises of “Shelter” is performed.